[quotation] On agricultural education - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On agricultural education: 'Farmer parents in developing countries mention biotechnology, information science and business management before they suggest agriculture... My feeling is that agricultural university training will more and more become...